Private governance and accounting for sustainability networks. (November 2016) - Thistlethwaite, Jason; Paterson, Matthew
Accounting rules and practices have become an important component of the governance of sustainability, notably in the field of corporate environmental, social, and governance reporting. This paper analyses the emergence and character of private governance initiatives regarding sustainability accounting. It does so using social network analysis in order to be able to conceptualize the patterns of connection across these different initiatives, and thus contribute to three specific ways that these initiatives are understood theoretically—as privatized neoliberal governance, via notions of professional epistemic authority, and through the concept of experimentation and experimental governance.